Development of Fuzzy Algorithm as Mobility Aid for Blind Person Using Two Sensor Points: Visual Aid for Blind Person - Tata Supriyadi; Ridwan Solihin; Endang Habinuddin; Sudrajat Sudrajat (International Journal of Engineering Continuity, 2024)
White canes are an ideal choice for blind person to do independent mobility because of its relatively cheap price. However, whitecane has the disadvantage of only being able to identify objects in front of it when they have been touched and cannot provide a choice of direction. This study developed a prototype whitecane with a feature that can provide a choice of direction based on the results of identifying the distance of the object to its user. This prototype was designed and implemented using two ultrasonic sensors installed on the stick as a replacement for the spatial sensing system. Both distance data from the sensors are processed in the Arduino Nano microcontroller to carry out the Fuzzy process stages. Fuzzy input process, rule-based Fuzzy inference, and Defuzzification for decision output. The results of the decision are translated into voice information to the user. Experiments with three scenarios showed that the utilization of the system with constant contact O&M technique showed a success rate of 100% while the other two techniques were only 33.3%. So the constant contact O&M technique can support effective mobility for the use of assistive aids and can be developed into a new technique.